The Caesarean Section rate at Mowbray Maternity Hospital: Applying Robson's Ten group classification system - Venter, Eben Kruger (Department of Obstetrics and Gynaecology, 2019)
Background The United Nations (UN) aims to reduce the maternal mortality ratio (MMR) and improve access to reproductive health services. Caesarean sections (CS) are known to be associated with a raised mortality rate by a factor of 2.8 in addition to the raised morbidity rate (OR 3.1; 95% CI 3.0-3.3) compared to vaginal deliveries (VD). Globally, there has been a concerning trend in the caesarean section rate (CSR), rapidly increasing since the 1970’s, with some countries reporting CS rates as high as 40.5%. South Africa has a CSR of 25.7%, which is higher than the suggested rate by the World Health Organization (WHO) of 15%; a rate above which the WHO suggests no maternal and fetal benefit exists. Robson introduced a universal classification system for caesarean sections with 10 totally inclusive and mutually exclusive groups. Horak made use of the ten group classification system (TGCS) to calculate the CSR at Mowbray Maternity Hospital (MMH) and its referring midwife obstetric units (MOU) for 2009, and reported it as 20.7%. Since the completion of her study, the referral routes to MMH have changed and the management of HIV-associated illnesses has markedly improved. A period of 7 years has elapsed and it was thought to be an optimal time to repeat a review of the CSR and compare it with the rates from 2009. Objectives The study aims to calculate the CSR for MMH from January 2016 to June 2016. Analyses of the CSR within each Robson group will be done and compared to the rates from 2009. This will allow us to make recommendations, if appropriate, aimed at reducing the CSR. Methods A retrospective, observational study was performed at MMH in Cape Town. Data was collected from birth registers for January 2016 – June 2016. All women who delivered, including all caesarean sections and vaginal births, were entered into the study, provided the newborn was viable with a birth weight >500g. Parameters were recorded onto an electronic and password-protected Microsoft Excel® spreadsheet and were used to classify deliveries according to the Robson Classification system. To allow for comparison with Horak’s study, deliveries at MMH for January 2009 – June 2009 were selected and analyzed. All the data was analyzed with STATA software and presented in various graphical formats. Ethics approval was obtained from University of Cape Town’s Human Research Ethics Committee (HREC Ref: 539/2016). Results There were 4727 deliveries from January to June 2016, of which 2472 were vaginal births and 2255 were caesarean sections, giving rise to a CSR of 47.70% (95% CI 46.28- 49.13). Of all the caesarean sections performed, 62.7% were primary caesarean sections and 37.3% were repeat caesarean sections. Nulliparous women, compared to multiparous women without a history of a prior CS, were at higher risk for a CS if in spontaneous labour (OR 2.02; 95% CI 1.71-2.38) and if induced (OR 2.75; 95% CI 2.13- 3.53). Group 5 (women with a previous CS), with a CSR of 85.34% (95% CI 82.82-87.61) made the greatest contribution to the overall CSR. The overall CSR from January to June 2009 was 44.10% (95% CI 42.63-45.57), calculated from 4379 deliveries. There was a statistically significant increase in the CSR of 3.60% from 2009 to 2016. A similar significant increase was observed in the respective CS rates of Group 1 (5.59%), Group 2 (11.63%) and Group 10 (8.73%). Group 4 was the only group with a statistically significant decrease of 4.48% in its CSR. An additional 308 labour inductions were performed in 2016, however, women in 2016 were statistically significantly less likely to be successful in a vaginal delivery (OR 0.67; 95% CI 0.55-0.81 p<0.001) compared to women in 2009.